Ground-state conformers enable bright single-fluorophore ratiometric thermometers with positive temperature coefficients. (13th September 2017) - Chi, Weijie; Yin, Wenting; Qi, Qingkai; Qiao, Qinglong; Lin, Yuyan; Zhu, Zhuohui; Vijayan, Sindhu; Hashimoto, Michinao; Udayakumar, Gayathri; Xu, Zhaochao; Liu, Xiaogang
Abstract : A pseudo-rigid fluorophore with multiple conformers enables highly reliable single-fluorophore ratiometric temperature sensing. Abstract : Fluorescence thermometry based on organic dyes affords high spatial and temporal resolution with a simple system design and low cost, for measuring temperatures in microenvironments. Many fluorescent thermometers consist of two types of fluorophores with distinct temperature responses, and the ratios of their fluorescence intensities afford accurate temperature information. Yet, the reliability of these ratiometric thermometers is vulnerable to photobleaching induced system variations. In this paper, we have proposed and demonstrated a new strategy, to achieve ratiometric temperature measurements from 15 °C to 75 °C, based on ground-state conformational isomers of a single type of dye. These ground-state conformers emit bright fluorescence, in contrast to excited-state conformational changes that generally quench emissions. Moreover, thermal equilibrium of these conformers and their distinct spectra lead to ratiometric temperature readings that are not affected by photobleaching. We expect that our design strategy has significant implications for developing fluorescence thermometry with outstanding reliability.